Porosity effects of natural latex (Hevea brasiliensis) on release of compounds for biomedical applications - Miranda, M. C.R. [UNESP]; Prezotti, F. G. [UNESP]; Borges, F. A. [UNESP]; Barros, N. R. [UNESP]; Cury, B. S.F. [UNESP]; Herculano, R. D. [UNESP]; Cilli, E. M. [UNESP] (Taylor & Francis, 2017)
Natural rubber latex biomedical (NRLb) obtained from the rubber tree Hevea brasiliensis has shown great potential in biomedicine and biomaterial applications. NRLb has been utilized as a physical barrier against infectious agents and in the controlled release of drugs and extracts. In the present work, NRLb was polymerized in a lyophilizer using different volumes of water to control the resultant membrane porosity and characterized regarding the surface morphology, water vapour permeability (WVP), mechanical properties, haemolytic activity and cytotoxicity. The release of bovine serum albumin protein from the latex membranes was evaluated. Drug release rates increased with porosity and membranes were able to control protein release up to 12 h. In addition, WVP increased with the quantity of pores. The cell viability observed for the porous membrane was higher than that noted for conventional membranes. In summary, the porosity control of natural latex membranes can be used to modulate properties and make them suitable for biomedical applications, such as wound dressings, modulated gas-exchange membranes and controlled drug delivery systems.
Keywords: biomaterial; drug delivery; Lyophilized membrane; natural rubber latex; thermally Induced Phase Separation (TIPS)